Servant Leadership Reality Practice and its Impact on Job Involvement – A field Study on Administrative Staff of King Abdul-Aziz University - Female Section in Sulaymaniyah – - abid, Sakhaa Adnan; mufti, Yara Bassam; Al-Shamasi, Areej Abdel-Rahman (Journal of Economic, Administrative and Legal Sciences, 2021)
The aim of this research is to identify the role of servant leadership with its dimensions (empowering others- humility- accountability- acceptance-giving directions- Stewardship) in achieving job involvement for King Abdul-Aziz University female administrators. In order to fulfill the research objectives, descriptive analytical methodology was used, and questionnaire was utilized to collect the required data from (166) participants; the data were statistically analysesd. Several statistical functions were used on the collected date. The most important result is stated that there is an impact and a relationship between servant leadership and job involvement. Showing that, giving more attention to the practice of servant leadership behaviours may lead to the enhancement of KAU administrator's job involvement. Accordingly, this research introduces some recommendations, such as, giving leadership literature more concern by providing the organizations with new books and scientific journals about leadership types, competencies and traits; this will encourage employees to read them. Moreover, organization should focus on employee's job involvement; this may benefit the organization in a way that would give a higher impact on the employee's work desire, this in turn, can positively enhance organizational performance indicators such as; productivity, job turnover, job security, efficiency, effectiveness, and customer satisfaction. In addition, the organization should give more concern to provide a healthier workplace that could trigger the employees' enthusiasm, morality and job involvement; as a result, employees may gain a positive feeling and good impression towards achieving the organization goals.
Keywords: leadership; servant; involvement; career; subordinates; leader